Versatile use of vacuum-assisted healing in fifty patients - Al Fadhli Ahmad; Alexander George; Kanjoor James (Indian Journal of Plastic Surgery)
Context: Wound management can often be a challenging experience, especially in the presence of diabetes mellitus, vascular or immunological compromise. While no single technique can be considered by itself to be ideal, vacuum-assisted healing, which is a recent innovation, is fast becoming a necessary addition as adjuvant therapy to hasten wound healing. Aims: To determine the efficacy of vacuum-assisted healing. Settings and Design: Plastic surgery centre. Ministry of Health Hospital, Kuwait. Materials and Methods: Patients from Kuwait in a wide variety of clinical situations were chosen for study: Patients (n=50) were classified by diagnosis: Group 1: pressure sore- sacral (n= 3), trochanteric (n=6), ischial (n= 2); Group 2: ulcers (n= 11); Group 3: traumatic soft tissue wounds (n =15); Group 4: extensive tissue loss from the abdominal wall perineum, thigh and axilla (n =5); Group 5: sternal dehiscence wounds (n =4) and Group 6: wounds from flap necrosis (n =4). All wounds were subjected to vacuum by wall unit or portable unit, using pressure of 100-125 mm - continuous or intermittent. Closure of wounds, significant reduction in size and refusal by patient for continuation of vacuum-assisted closure therapy were end points of vacuum application. Results: Sixteen per cent of patients showed complete healing of the wound. Seventy per cent of patients showed 20-78% reduction in wound size. In 14% of patients treatment had to be discontinued. All patients showed improvement in granulation tissue and reduction in bacterial isolates and tissue oedema. Conclusions: The application of subatmospheric pressure or negative pressure promotes healing in a wide range of clinical settings and is an advanced wound healing therapy that can optimize patient care, promote rapid wound healing and help manage costs. It may be used in most instances in both hospital and community settings.